2018
DOI: 10.1093/jee/toy239
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Seasonal Abundance of Auchenorrhyncha With a Focus on Potential Insect Vectors of Xylella fastidiosa in Olive Orchards in Three Regions of Greece

Abstract: Studies of the species composition, seasonal appearance, and abundance of Auchenorrhyncha in olive crops is of paramount importance to reduce the potential of Xylella fastidiosa to invade new areas. As similar investigations had not previously been conducted in Greece, extensive surveys were undertaken in olive orchards located in three of the most important regions for olive production in central Greece (Fthiotida), south-central Greece (Attica), and southern Greece (Chania). Surveys took place over a 13-mo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 20 publications
4
21
0
3
Order By: Relevance
“…During the summer, the situations in Apulia and Liguria olive groves were clearly different: In Apulia, the number of spittlebugs collected in the olive agroecosystem during hot months was low, while in Liguria, spittlebugs were collected inside the olive groves in relatively high numbers until autumn. The continuative presence of spittlebugs on olive trees and in the agroecosystem is probably related to the less severe water stress of olive trees growing in Liguria compared to Apulia, Spain, and Greece, where adults almost disappear in summer from the olive agroecosystem [1,[5][6][7]34]. Such a difference in crop exploitation may have important consequences if X. fastidiosa were introduced in Liguria, since the prolonged presence of vectors on the crop trees may contribute to the higher spread of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the summer, the situations in Apulia and Liguria olive groves were clearly different: In Apulia, the number of spittlebugs collected in the olive agroecosystem during hot months was low, while in Liguria, spittlebugs were collected inside the olive groves in relatively high numbers until autumn. The continuative presence of spittlebugs on olive trees and in the agroecosystem is probably related to the less severe water stress of olive trees growing in Liguria compared to Apulia, Spain, and Greece, where adults almost disappear in summer from the olive agroecosystem [1,[5][6][7]34]. Such a difference in crop exploitation may have important consequences if X. fastidiosa were introduced in Liguria, since the prolonged presence of vectors on the crop trees may contribute to the higher spread of the bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…The most important differences between the two areas concerned (i) host-plant association that, besides being determined by insect preference, was driven by ground cover floral composition, (ii) summer colonization of olive trees by adults, that visited olive canopies in a higher number and for a prolonged period in Northern Italy, and (iii) spittlebug population level that appeared to be higher in Northern Italy. Actually, several reports indicated that the populations of P. spumarius and of other spittlebug species are quite low under warm and dry Mediterranean conditions [6,7], although with some exceptions [8]. The knowledge of preferential plant selection by both nymphal and adult stages of the main X. fastidiosa vector in Europe may allow designing more effective integrated pest management programs, so far based on soil tilling to eliminate nymphs and on insecticide applications targeting adults on the crop canopy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other protocols and sampling techniques for studying migration of spittlebugs from cultivated to unmanaged areas should be considered. Accordingly, Tsagkarakis et al (2018) [42] proposed Malaise traps as an alternative sampling method of Auchenorryncha in olive groves. These authors stated that Malaise trapping was better than sweep netting for studies on the species richness and the identification of potential vectors of X. fastidiosa .…”
Section: Discussionmentioning
confidence: 99%
“…Tsagkarakis et al (2018) [42] described a bivoltine cycle for spittlebugs in Greece. Likewise, Drosopoulos and Asche (2001) [50] described the bivoltine life cycle of P. spumarius in Greece.…”
Section: Discussionmentioning
confidence: 99%
“…While the amount of information on the phenology and ecology of P. spumarius and closely related species is rapidly increasing [11][12][13][14][15][16][17][18][19], the literature on biological control agents of these insects is very scarce. Indeed, it is restricted to reports on the presence of egg parasitoids of the genus Ooctonus (Hymenoptera Mymaridae) and Centrodora (Hymenoptera Aphelinidae), the endoparasitoid Verrallia aucta FallĂ©n (Diptera Pipunculidae) and few uncharacterized entomopathogenic fungi (revised in [8,14]).…”
Section: Introductionmentioning
confidence: 99%